(untitled) (Annals of Medical Research, 2022)
Aim: Pedicled abdominal and groin flaps have been used for hand and forearm reconstruction for years. Nowadays, they are applied as a safe option when free flap is not suitable. In this study, we aimed to present cases in which soft tissue defects on hand and forearm were closed with pedicled groin and abdominal flaps, in the light of the literature. Materials and Methods: Thirty-five patients whose soft hand tissue defects in the hand and forearm were treated with pedicled groin and abdominal flaps in the department of Plastic, Reconstructive and Aesthetic Surgery between 2010 and 2022 were included in the study. Data such as age, gender, cause of defect, localization of defect, size of defect, donor site closure method, flap division time, hospitalization time and complications which were obtained from patient files were evaluated. Results: Our patients were between the ages of two and 65 and mean age was found as 33.9 ± 15,7. Thirty-one (88.5%) of our patients were male, while four (11.5%) were female. When the causes of defects were examined, it was found as crush injuries of hand and fingers in 12 patients (34.29%), electrical burn in 11 patients (31.43%), gunshot wounds in five patients (14.28%), degloving injury in four patients (11.43%) and snake bite in three patients (8.57%). All flap donor sites were closed primarily. Flap loss was not recorded. Conclusion: Pedicled abdominal and groin flaps, which are a fast and safe option, continue to be an important alternative in suitable patients despite the advances in microsurgery.